Le tesi di laurea nelle biblioteche di architettura - Serena, Sangiorgi (Proceedings e report, 2003)
There is no general legislative framework for theses, although a number of solutions have been devised at local level which may be significant for Italian university librarians. The problems are numerous and of different kinds: technical, copyright-related and also more strictly bound up with library science, such as cataloguing, conservation and access. Each library appears to have devised original approaches, and it is important to make these known in order to offer suggestions for the treatment of this documentary heritage that is still difficult to access.